2009
DOI: 10.1002/jrs.2245
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarbon materials: probing the curvature and topology effects using phonon spectra

Abstract: Much has been learned from the use of resonance Raman spectroscopy and high-resolution transmission electron microscopy techniques about the micro-/nanoscopic structure of various nanostructured carbons. However, they still possess some features that are not entirely understood particularly in terms of topological characteristics, which go beyond making a distinction with just the geometrical structure at nanoscale. To effectively utilize the potential of these materials for technological needs, understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 85 publications
4
63
0
Order By: Relevance
“…When curvature increases with no defects, R Tor increases because curvature enhances the 2*D1 band intensity compared to that for mostly planar graphene layers (Larouche & Stansfield 2010;Gupta & Saxena 2009). If the number of defects is increasing, R Tor decreases.…”
Section: Astrophysical Implications Of the Nanostructurationmentioning
confidence: 99%
See 1 more Smart Citation
“…When curvature increases with no defects, R Tor increases because curvature enhances the 2*D1 band intensity compared to that for mostly planar graphene layers (Larouche & Stansfield 2010;Gupta & Saxena 2009). If the number of defects is increasing, R Tor decreases.…”
Section: Astrophysical Implications Of the Nanostructurationmentioning
confidence: 99%
“…It was shown that, depending on the flame conditions, flat to strongly curved native nanoparticles may be produced (Violi 2004). Curvature due to the presence of defects, such as pentagonal rings, within the polyaromatic unit leads to spherical structures, while perfectly hexagonal graphene sheet can form only tubular-type curvature (Gupta & Saxena 2009). Tortuosity A40, page 10 of 14 is associated with reticulation due to small aliphatic bridges that link different polyaromatic units.…”
Section: Astrophysical Implications Of the Nanostructurationmentioning
confidence: 99%
“…In general, all absorption spectral bands arising in UV-Vis range of the electronic spectra of heteropoly compounds containing Keggin polyanion [ [55,56]. Raman spectroscopy is widely used non-destructive technique for the characterization of carbon-based materials [57] and POMs [58][59][60], M = Mo and W since it is highly sensitive to local structure and lattice vibrational bonding configurations within molecules and their interactions with graphene. Keggin-type HPAs are formed by assembling three MO 6 octahedra by edge-sharing oxygen atoms (M-O c -M) to form M 3 O 13 sets, which further condense by sharing corner oxygen atoms (M-O b -M) around a central atom (P or Si) to form a cage.…”
Section: Optical and Vibrational Spectroscopymentioning
confidence: 99%
“…[5,13] As a result, only the E 2g symmetry in-plane optical mode (G line at 1582 cm −1 ), associated with the stretching of all C C pairs, is detected in its first-order Raman spectrum (spectrum (a) in Fig. 1).…”
Section: Raman Scattering In Graphite and Graphiterelated Carbonsmentioning
confidence: 99%
“…In recent years, attention, initially focused on nanostructures with simple geometries (planar: graphene; [3] tubular: single-, double-and multi-walled CNTs; [2] spherical/spheroidal: fullerenes, onion-like carbon, nanocages [4] ) has been extended to C sp 2 allotropic forms with complex geometries (nanorings, nanocones, nanohorns, nanodisks, Y, T and X junctions, twisted ribbons). [5] However, in spite of the great proliferation of novel and attractive nanocarbons, CNTs still play a leading role in nanotechnologies, involving the most disparate application fields, from nanoelectronics [6] to medicine. [7] Single-and multi-walled carbon nanotubes (SWCNTs and MWCNTs) are successfully synthesised by a number of methods.…”
Section: Introductionmentioning
confidence: 99%